(untitled) (Jurnal De Jure Muhammadiyah Cirebon, 2017)
The mindset of the elite class in the formulation of legislation. In the context of the formation of the Act, freedom of expression is a condition for listening to popular opinions. Listening aims to know the opinions of all the people, not a few people. Such knowledge will be the basis of legislative consideration in approving a bill. However, the mindset of the elite class is sometimes confusing even still see the formation of legislation should impose its will. At the level of application the community becomes a victim due to the mindset of an elite class that is not yet mature enough in thinking related to its task. Keywords: the formulation of legislation, legislative and elite class.